Antidepressant like activity of Buspirone but not of ondansetron when administered in combination with Fluoxetine or Desipramine in mice - Verma, Veena; Banerjee, Biswadeep; Mehta, Ashish K. (International Journal of Basic & Clinical Pharmacology, 2021)
Background: The involvement of one or more 5-HT receptor sub-types in the pathophysiology of depression is still unclear. The study was performed to investigate the effect of ondansetron and buspirone on depression, and their interaction with fluoxetine or desipramine. Methods: The mice were administered ondansetron, buspirone alone and in combinations with fluoxetine or desipramine for 21 days, and the antidepressant effect was assessed by the immobility period and the sucrose consumption, on the tail suspension test (TST) and the chronic mild stress (CMS) models, respectively. Results: Both ondansetron and buspirone when given alone demonstrated slight non-significant decrease in the immobility time in TST model. Ondansetron when given in combination with fluoxetine (10 mg/kg; i.p.) and desipramine (15 mg/kg; i.p.), showed significant decrease in immobility time in comparison to the control group only. On the other hand, both the combinations of buspirone, either with fluoxetine or desipramine showed significant decrease in the immobility time when compared to the respective group. In CMS, the fluoxetine, desipramine, ondansetron, and buspirone showed gradual increase in the sucrose consumption, at the end of 4th, 5th, and 6th week, but the significant effect was observed only at the end of 6th week, as compared to the control. The combination of buspirone with desipramine but not with fluoxetine showed significant increase in sucrose consumption when compared to respective group. Conclusions: Therefore, the study indicates that both buspirone and ondansetron have a potential antidepressant like action, although buspirone has shown better antidepressant activity than ondansetron as observed in various combination groups.